Enhancing Milling Surface Finish: The Role of Servo Parameters and Machining Stability - Su, Zheng-Mou; Lin, Wei-Zhu; Lin, Yung-Chih; Hung, Jui-Pin (Engineering, Technology & Applied Science Research, 2024)
Abnormal machining vibrations and inconsistent machining quality are commonly observed in high-speed machining operations and are often attributed to the inappropriate characteristics of servo dynamics and structural resonance caused by feeding motions with higher jerk. An understanding of the manner in which distinct servo system parameters impact machining, can facilitate the refinement of machine tool tuning, thereby enabling the achievement of desired machining outcomes. In practical terms, the servo parameters, including feeding acceleration and jerk, control gains, and feed-forward compensation, can be appropriately determined based on the characteristics of the machine in question, such as the presence of dynamic errors in positioning and contouring paths. This study aims to evaluate the interactive effects between servo parameters and machining parameters to gain insight into their influence on machining quality. In order to achieve this objective, different servo parameters were tuned to meet various machining requirements, and cutting experiments were conducted with consideration of the cutter stability. The results are expected to provide guidance on the control of servo systems and the optimization of machining parameters, ensuring that servo tuning effectively enhances machine tool cutting performance.